Hubungan Penggunaan Special Tool Terhadap Proses Pemasangan Pin Pada End Arm Excavator Pc200 - M. Hilmi Syiva Afiat; Asrori Asrori (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Working in the mining sector has a fairly high occupational risk, especially for mechanics in carrying out heavy equipment maintenance. One of the maintenance carried out is the replacement of the excavator bucket. The excavator bucket is mounted on the end arm of the excavator which is connected using a locking pin. The pin installation process is carried out by hitting with a hammer, where this process has a number of occupational risks such as being hit, exposed to material, and fatigue which can result in work accidents. This study aims to minimize the occurrence of occupational risks by finding out the relationship between the use of special tools on safety and job duration for the locking pin installation process. The method used is experimental quantitative method and using fishbone diagram. By using a special tool, the installation of locking pins becomes safer because the factors that cause accidents when using palju can be eliminated and the manpower required becomes more efficient, but in terms of time it requires a longer duration due to the limitations of the tool that requires adjustment several times when used.